When to Use Transdisciplinary Approaches for Environmental Research - Kiatkoski Kim, Milena; Douglas, Michael M.; Pannell, David; Setterfield, Samantha A.; Hill, Rosemary; Laborde, Sarah; Perrott, Laura; Álvarez-Romero, Jorge G.; Beesley, Leah; Canham, Caroline; Brecknell, Anthea (Frontiers in Environmental Science, 2022)
Transdisciplinary research (TDR) can help generate solutions to environmental challenges and enhance the uptake of research outputs, thus contributing to advance sustainability in social-ecological systems. Our aim is to support investment decisions in TDR; more specifically, to help funders, researchers, and research users to decide when and why it is most likely to be worth investing in TDR approaches. To achieve our aim, we: (1) define TDR and use a decision tree comparing it with alternative modes of research (i.e., basic, applied, disciplinary, multi-disciplinary, and interdisciplinary research) to help researchers and funders distinguish TDR from other research modes; (2) identify features of the research problem and context (complexity, diverse knowledge systems, contestation, power imbalance, and disagreement on the need for transformative change) where a TDR approach could be more appropriate than the alternative research modes; and (3) explore the idea that the intensity of the contextual features in (2), together with the problem at hand, will help determine where a research project stands in a continuum from low- to high-TDR. We present five studies exemplifying lower- to higher-TDR approaches that are distinguished by: (a) the number and variety of research participants engaged; (b) the strength of involvement of non-academic actors; and (c) the number and variety of disciplines and knowledge systems involved in the research.